Weighted Density Center (WDC-LEACH-C) Clustering Protocol for Wireless Sensor Networks (WSN) - Slimani, Amira; Redjimi, Mohammed; Slimani, Djamel (Informatica, 2017)
Wireless sensor networks (WSNs) are composed of a huge number of micro sensors. These tiny devices are characterized by low energy battery and low processing capability, so the most critical challenge in these networks is the energy conservation. Hierarchical architecture with clustering of nodes is suitable for solution of many problems in WSN and has many benefits as energy efficiency, data aggregation and scalability. Low Energy Adaptive Clustering Hierarchy (LEACH) and its centralized version LEACH-C are the most important hierarchical protocols. This paper proposes a cluster based routing protocol for WSNs (WDC-LEACH-C) which is an improvement of LEACH-C that is based on the weighted density center and energy criteria in the selection of the cluster head (CH). The proposed protocol provides its effectiveness in increasing network lifetime and energy efficiency. Simulation results show that the proposed algorithm performs better than LEACH-C, Impro-LEACH and DE-LEACH algorithms.